Mining Permits for Religion Organizations in Indonesia: Public Interest vs Islamic Ethics - Muh. Yunus; Zulkifli Aspan; Resi Resi; Maskun Maskun; Rasyida Usman; Azlan Thamrin (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2025)
This study critically examines the Indonesian government's policy of granting mining permits to religious organizations, which has given rise to various interpretations and ethical polemics because it is not in line with Law Law Number 3 of 2020 concerning Mineral and Coal Mining (Minerba Law) and Government Regulation Number 25 of 2024 concerning the Implementation of Mineral and Coal Mining Business Activities. This research focuses on analyzing this legal disharmony while evaluating the ethical implications through the perspective of Islamic environmental ethics. With a community service approach based on juridical and conceptual analysis, this study links the theory of law enforcement with Islamic ethical principles, including fiqh al-bi'ah, maqāṣid al-sharī'ah, and the concept of amanah. The results of the study show regulatory inconsistencies and ethical weaknesses in policies that place religious organizations as political-economic actors, thereby potentially weakening their moral authority, neglecting ecological sustainability, and disregarding justice and the public interest. The recommendation that can be offered is the need for policy reform that affirms the role of religious organizations not as economic actors in mining, but as moral and ethical guardians in the management of natural resources. This reform needs to be realized through multi-stakeholder participation, the strengthening of legal instruments that are in line with religious values and environmental ethics, and oversight mechanisms that ensure that mining management is truly directed towards public welfare and ecological sustainability.